Education on the Importance of Immunization for Infants at Puskesmas Tamalanrea Jaya Makassar City - Sri Wahyuni; Asridawati Asridawati; Rukinah Rukinah; Rosmiaty Pammu; Ria Wahyuni; Dewi Yanti Rumagutawan; Santi Rumfot (Jurnal Pengabdian Masyarakat Edukasi Indonesia, 2024)
Immunization of infants is one of the most important steps in maintaining their health and well-being. This article discusses the importance of immunization in infants, including its benefits, the types of immunizations recommended, and their positive impact on society. Immunization in infants helps protect them from serious diseases that can be life-threatening, such as measles, polio, tetanus, and hepatitis. By immunizing babies according to the schedule recommended by health authorities, parents can help build the baby's immune system so that they are more resistant to infection and disease. In addition to protecting vaccinated babies, immunization also plays an important role in creating herd immunity. With high vaccination rates in communities, infectious diseases have little chance of spreading, protecting even individuals who cannot yet be vaccinated or who are immune to the disease. There are still many myths and concerns about immunization that can deter parents from immunizing their babies. Therefore, it is important for medical personnel and health professionals to provide accurate education about the benefits of immunization and help answer questions and concerns parents may have. By understanding the importance of immunization for infants, it is hoped that public awareness will increase and vaccination rates will continue to increase. This will result in a healthier generation and reduced morbidity and death from immunization-preventable diseases.